A New Productivity Benchmarking System Connected to Well-designed Labour Apprenticeship Framework for Construction Projects (Construction Economics and Building, 2023)
This study primarily identifies the knowledge gaps that must be filled to apply conceptualised methods for rising and benchmarking productivity levels of various construction operational tasks. Accordingly, this study intended to evaluate labour productivity in relation to labour performance using potential apprenticeship instruments and systems. Comprehensive literature analysis and expert consultations were carried out to create a new mechanism with the collection of potential models, methods and systems connected to labour training, performance evaluation and productivity measurements. A total of 23 construction projects in Sri Lanka employed the created approach methodically. The results demonstrate the precise patterns of substantial shifts in labour productivity and performance index values, which have sparked new conceptual mechanisms for construction project planning methods. The outcomes demonstrate that the suggested approach can be used in a way that is reliable, generalisable, productive and sustainable. The study provides project managers, planners and engineers with a new road map and helpful techniques to raise the standard for measuring labour productivity levels across a variety of jobs. The overall study outcomes strengthen the chain relationship among the training elements, labour skills, performance and productivity. Though the study findings were limited to the construction industry and Sri Lankan context, the study outcomes are expected to make a significant impact on the current practices of various industry sectors in many developing countries for achieving higher productivity levels in work operations. This paper discusses some more implications and future scopes of the study elaborately.